EFFECT OF CORE SERVICES , MECHANICAL SERVICES , SERVICES PERIPHERALS ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN AC AUTO REPAIR SPECIALIST PROTECH SEMARANG - Mutma’inah Mutma’inah; Tsalist Saefuddin; Heru Sri Wulan (Jurnal Ekonomi dan Bisnis Kontemporer, 2016)
his research aims to determine whether the presence or absence of the effect of CoreServices, Mechanical Services and Peripherals Services Satisfaction and loyalty in ProtechAuto Ac Repair Specialist Semarang. The methode in this study is to collect datakuisioner.Sampel in this study were 60 responden.Teknik data analysis used is multiplelinear regression.The data analysis technique used to test this hypothesis is multiple linear regressionanalysis that includes Regression Testing, Test F, T test and Coefficient of Determination.All data were processed using SPSS 20.0 program were first tested using ClassicalAssumption Test covering Normality Test and Test HeteroskidastityResults Test F shows that the Service Core Services Mechanical and ServicesPeripherals for Consumer Satisfaction and Loyalty Consumers Workshop Protech Auto AirConditioning Specialist significant since F count F table (59 415 2.77), while from thecalculation of T test each independent variable shows the core services, MechanicalServices, Services and Peripherals significant influence.Keywords : core services, mechanical services, peripherals and services for consumersatisfaction and customer loyalty